INDONESIA’S MARITIME TRANSFORMATION: FROM MARITIME HERITAGE TO SUSTAINABLE BLUE ECONOMY - Latif, Ninit Setyanti; Giri, Puput Indah; Yulifar, Leli (Yayasan Amanah Nur Aman, 2025)
This study analyzes Indonesia’s maritime transformation from its historical maritime heritage to the implementation of a sustainable Blue Economy. Employing a qualitative descriptive method through literature review, this research integrates historical and geopolitical approaches using content analysis. Primary sources include government policy documents, while secondary materials consist of historical literature, academic journal articles, and reports from international organizations. The findings reveal that the legacy of the Spice Route and the Asia-Africa maritime trade network shaped Indonesia's maritime identity, though colonialism redirected development toward a continental orientation that weakened maritime capacity. The revitalization of maritime strategies through the Global Maritime Fulcrum and Blue Economy has promoted sustainable utilization of marine resources including fisheries, marine tourism, renewable energy, and biotechnology, despite facing challenges in regulation, technology, and ecosystem conservation. These developments have enhanced Indonesia's geopolitical leverage in the Indo-Pacific region, strengthened maritime sovereignty, and supported national diplomacy. The Blue Economy framework offers substantial opportunities for Indonesia to optimize its maritime potential while maintaining environmental sustainability and supporting coastal communities'’ welfare.